From Bench to Booth: Examining Hair Cell Regeneration Through an Audiologist's Scope - Lewis, Rebecca M. (Journal of the American Academy of Audiology, 2021)
Damage to auditory hair cells is a key feature of sensorineural hearing loss due to aging, noise exposure, or ototoxic drugs. Though hair cell loss is permanent in humans, research in bird species led to the discovery that analogous hair cells of the avian basilar papilla are able to regenerate after being damaged by ototoxic agents. Regeneration appears to occur through a combination of the mitotic expansion of a precursor population of supporting cells and direct transdifferentiation of supporting cells into functioning hair cells. This review will synthesize the relevant anatomy and pathophysiology of sensorineural hearing loss, the historical observations that led to the genesis of the hair cell regeneration field, and perspectives on initial human hair cell regeneration trials.
Keywords: hearing; auditory; cochlear implants